The Relation Between 25-Hydroxyvitamin D Levels and Sepsis in Neonatal Intensive Care Unit Infants: A Comprehensive Systematic Review - Nurul Purnamasari; Ririn Azhari (International Medical Journal Corp. Ltd, 2025)
Introduction: Neonatal sepsis is a leading cause of morbidity and mortality worldwide, characterized by a dysregulated host immune response to infection. Vitamin D, recognized for its potent immunomodulatory functions, has been implicated as a potential modifiable risk factor. This systematic review aims to comprehensively evaluate the association between 25-hydroxyvitamin D levels and the incidence and severity of sepsis in infants admitted to the Neonatal Intensive Care Unit (NICU). Methods: A systematic search of PubMed, Scopus, and the Cochrane Library was conducted to identify observational (case-control and cohort) studies assessing maternal, cord, or neonatal 25(OH)D levels in NICU infants with and without sepsis. Data on study characteristics, participant demographics, vitamin D status, and a minimum of 15 clinical and laboratory outcomes were extracted. The methodological quality of included studies was assessed using the Newcastle-Ottawa Scale (NOS). Results: The review included a robust selection of observational studies. A consistent and statistically significant association was found between lower 25(OH)D levels and the presence of neonatal sepsis. Neonates with sepsis had markedly lower mean 25(OH)D concentrations compared to non-septic controls across multiple studies. Furthermore, low maternal and cord blood 25(OH)D levels were identified as significant independent risk factors for developing neonatal sepsis, with neonates born to vitamin D-deficient mothers having substantially increased odds of infection. Vitamin D deficiency was also significantly associated with increased sepsis severity, longer hospital and NICU stays, greater need for mechanical ventilation and inotropic support, and adverse laboratory profiles, including elevated C-reactive protein (CRP) and lower platelet counts. Discussion: The evidence strongly suggests that pre-existing vitamin D deficiency is a critical predisposing factor for neonatal sepsis, rather than merely a consequence of the acute illness. The immunomodulatory role of vitamin D—enhancing innate antimicrobial defenses while tempering excessive inflammation—provides a strong biological rationale for these clinical findings. Low vitamin D status appears to impair the neonate's ability to mount an effective yet controlled immune response, thereby increasing susceptibility to infection and the risk of progression to severe sepsis and organ dysfunction. Methodological challenges, including variability in 25(OH)D assays and the unmeasured influence of Vitamin D Binding Protein (VDBP), are important limitations in the current literature. Conclusion: There is a robust association between vitamin D deficiency and an increased risk and severity of neonatal sepsis. Optimizing perinatal vitamin D status represents a promising preventative strategy. High-quality, large-scale randomized controlled trials are urgently needed to establish causality and to formulate evidence-based guidelines for vitamin D supplementation in pregnant women and high-risk neonates for the prevention of sepsis.